End of story : a novel [large type] - Finn, A. J. (Harper Large Print, an imprint of HarperCollinsPublishers, 2024)
Invited by a reclusive mystery novelist to help draft his life story, a longtime correspondent and detective fiction expert finds herself in a real whodunnit when she learns the writer's first wife and son mysteriously vanished.